The Composition and Relative Abundance of Fish Species in a Mangrove Creek in the Niger Delta, Nigeria, Based on Different Types of Gear: Fish Relative Abundance in Mangrove Creek (Biological Sciences - PJSIR, 2011)
The composition and relative abundance of fish species assemblage of a mangrove creek in the Niger Delta, Nigeria based on different types of gear was assessed at four stations between November 2004 and June 2006. The overall community structure was made up of 25 species of 16 families. Visual observation showed that tilapia species comprising of Sarotherodon melanotheron and Tilapia guineensis were the most dominant species. Samples from baited entrance traps indicated that S. melanotheron dominated T. guineensis. Samples from baited hook and line, and cast net showed dominance of P. elongatus followed by P. quadrifilis. (The baited hook and line is commonly used by the fishers because it is effective in catching diversity of species, except that it is unable to catch bottom feeders such as mullets and tilapia species). Funnel entrance trap had the highest species selectivity, catching only tilapia species. Cast net was more selective in species catch than baited hook and line, but it was effective in catching both pelagic and benthic species. Among the fish species, members of the families: Sciaenidae, Polynemidae, Ariidae, Monodactylidae and Cichlidae were permanent residents; Carangidae, Luthjanidae and Serranidae were temporary residents; while Elopidae, Gobiidae, Dasyatidae, Cynoglossidae, Sphyraenidae and Trichiuridae were rare species.Keywords: composition